Characteristics of Cell-bound Lipase Production by a Newly Isolated Strain of Aspergillus flavus - Che Omar, Ibrahim; Ilias, Nooraini (Universiti Putra Malaysia Press, 1996)
An isolate of Aspergillus flavus was found to be a potential producer of cell bound lipase. A maximum lipase production of about 32 U/g dried biomass occurred after 36 h of cultivation. The enzyme production remained constant thereafter. The lipase activity of the fungus was not greatly influenced by the presence of various carbon and nitrogen sources and lipid materials in the basal medium. During the period of maximum synthesis of cell-bound lipase, a significant increase in the extracellular lipase was also detected in the culture medium. However, extracellular lipase was found to be extremely unstable. The activity of cell-bound lipase was stable at 55°C and retained 100% of its activity after 24 h at this temperature. The lipase activity can also be stimulated by the presence of sodium taurocholate and ZnC12 . The lipase exhibited a wide range of substrate specificity on the hydrolysis of lipid materials